Interviewing for Journalists / Second Edition - Adams Sally; Hicks Wynford (Rouledge, 2009)
This book details the central journalistic skill of how to ask the right question in the right way. Introduction, Basics of Communicating and Interviewing, Preparing for Interviews: Face-to-Face and Telephone, Interviewing Techniques, Understanding Interviewees and Avoiding Problems, Quotes and Checking Your Information, Note-Telling and Recording, Interviewing for the Internet, Interviewing Politicians, Interviewing Celebrities, Law and Ethics, Appendices, Glossary, Recommended Books and Films, Index.